Polyvinylpyrrolidone as an Efficient Stabilizer for Silver Nanoparticles. Issue 9 (20th July 2014) - Huang, Weidong; Zhang, Linxia; Yang, Qiuping; Wang, Zhimin
Abstract Aggregation of nanoparticles is a serious problem in their applications. In this article, stability of biosynthesized silver nanoparticles (AgNPs) was initially studied with different concentrations of sodium chloride (NaCl). Surfactant screening showed that polyvinylpyrrolidone (PVP) was an ideal stabilizer, which not only was effective at a low concentration (0.1%, V/V), but also could protect silver colloids from aggregation for a long period at 1 mol·L−1 NaCl, and 6 h even at 3 mol·L−1 NaCl. However, some other surfactants, such as sodium dodecyl (SDS), Triton X‐100, Tween‐20, and Tween‐80, could not prevent AgNPs from aggregation even at a high concentration up to 0.5% (V/V). This AgNPs stabilizer is simple and convenient for a variety of applications compared with others.